The Browser Hacker's Handbook - Alcorn, Wade (Wiley, 2014)
Hackers exploit browser vulnerabilities to attack deep within networks The Browser Hacker''s Handbook gives a practical understanding of hacking the everyday web browser and using it as a beachhead to launch further attacks deep into corporate networks. Written by a team of highly experienced computer security experts, the handbook provides hands-on tutorials exploring a range of current attack methods. The web browser has become the most popular and widely used computer "program" in the world. As the gateway to the Internet, it is part of the storefront to any business that operates online,; Includes bibliography and index